Distributed server-based rendering device and method - QU JIANGXUE; CAI WEIGUO; GONG HE; MO ZHENHAO; LIN JUN; TAO CHAO; LU SHIYOU; ZENG YILUN; SUN YANGFU; LIAO TIANLAN (2023)
The invention discloses a distributed server-based rendering device, and the device comprises a management server which is in communication connection with a client, and is used for receiving a rendering request sent by the client, carrying out the analysis of the rendering request, obtaining a rendering data parameter and a rendering mode according to an analysis result, and obtaining a UE4 instance starting strategy through the matching of the rendering mode; and the rendering server is connected with the management server and is used for starting the corresponding UE4 instance according to the UE4 instance starting strategy, controlling the corresponding UE4 instance to call the corresponding rendering node to perform rendering according to the rendering data parameter, and sending a rendering result to the management server. Therefore, the management server sends the rendering result to the corresponding client according to the rendering mode to display the rendering picture. The problem that an existing